QTL mapping of multiple foliar disease and root-lesion nematode resistances in wheat - Rebecca S. Zwart; Thompson, J. P.; Milgate, A. W.; Bansal, Urmil K.; Williamson, P. M.; Raman, H.; Bariana, Harbans S. (Molecular Breeding, 2010)
A genetic linkage map, based on a cross between the synthetic hexaploid CPI133872 and the bread wheat cultivar Janz, was established using 111 F(1)-derived doubled haploid lines. The population was phenotyped in multiple years and/or locations for seven disease resistance traits, namely, Septoria tritici blotch (Mycosphaeralla graminicola), yellow leaf spot also known as tan spot (Pyrenophora tritici-repentis), stripe rust (Puccinia striiformis f. sp. tritici), leaf rust (Puccinia triticina), stem rust (Puccinia graminis f. sp. tritici) and two species of root-lesion nematode (Pratylenchyus thornei and P. neglectus). The DH population was also scored for coleoptile colour and the presence of the seedling leaf rust resistance gene Lr24. Implementation of a multiple-QTL model identified a tightly linked cluster of foliar disease resistance QTL in chromosome 3DL. Major QTL each for resistance to Septoria tritici blotch and yellow leaf spot were contributed by the synthetic hexaploid parent CPI133872 and linked in repulsion with the coincident Lr24/Sr24 locus carried by parent Janz. This is the first report of linked QTL for Septoria tritici blotch and yellow leaf spot contributed by the same parent. Additional QTL for yellow leaf spot were detected in 5AS and 5BL. Consistent QTL for stripe rust resistance were identified in chromosomes 1BL, 4BL and 7DS, with the QTL in 7DS corresponding to the Yr18/Lr34 region. Three major QTL for P. thornei resistance (2BS, 6DS, 6DL) and two for P. neglectus resistance (2BS, 6DS) were detected. The recombinants combining resistance to Septoria tritici blotch, yellow leaf spot, rust diseases and root-lesion nematodes from parents CPI133872 and Janz constitute valuable germplasm for the transfer of multiple disease resistance into new wheat cultivars.
Keywords: Pratylenchyus spp; Pyrenophora tritici-repentis; Rust diseases; Septoria tritici blotch; Synthetic hexaploid wheat; Triticum aestivum

Inheritance of resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) in five doubled-haploid populations of wheat - Thompson, John P.; Rebecca S. Zwart; Butler, David (Euphytica, 2012)
Nematode species Pratylenchus thornei and P. neglectus are the two most important root-lesion nematodes affecting wheat (Triticum aestivum L.) and other grain crops in Australia. For practical plant breeding, it will be valuable to know the mode of inheritance of resistance and whether the same set of genes confer resistance to both species. We evaluated reactions to P. thornei and P. neglectus of glasshouse-inoculated plants of five doubled-haploid populations derived from five resistant synthetic hexpaloid wheat lines, each crossed to the susceptible Australian wheat cultivar Janz. For each cross we determined genetic variance, heritability and minimum number of effective resistance genes for each nematode species. Distributions of nematode numbers for both species were continuous for all doubled-haploid populations. Heritabilities were high and the resistances were controlled by 4-7 genes. There was no genetic correlation between resistance to P. thornei and to P. neglectus in four of the populations and a significant but low correlation in one. Therefore, resistances to P. thornei and to P. neglectus are probably inherited quantitatively and independently in four of these synthetic hexaploid wheat populations, with the possibility of at least one genetic factor contributing to resistance to both species in one of the populations. Parents with the greatest level of resistance will be the best to use as donor parents to adapted cultivars, and selection of resistance to both species in early generations will be optimal to carry resistance through successive cycles of inbreeding to produce resistant cultivars for release.
Keywords: Aegilops tauschii; Disease resistance; Durum wheat; Germplasm development; Triticum aestivum; Wheat breeding

Microsatellite mapping identifies TTKST-effective stem rust resistance gene in wheat cultivars VL404 and Janz - Bansal, Urmil K.; Rebecca S. Zwart; Bhavani, Sridhar; Wanyera, Ruth; Gupta, Vidya; Bariana, Harbans S. (Molecular Breeding, 2012)
Wheat cultivar VL404 carries seedling resistance to Puccinia graminis f. sp. tritici pathotype TTKST. Monogenic segregation for seedling resistance was observed in a VL404/WL711 recombinant inbred line population and the resistance locus was temporarily designated SrVL. Bulked segregant analysis using Diversity Arrays Technology markers located SrVL on chromosome 2BL. Detailed simple sequence repeat mapping placed SrVL between gwm120 and wmc175, both at genetic distances of 3.3 cM. Based on adult plant responses of Janz and VL404 in India and Kenya, we expected these cultivars to carry the same gene against TTKST. A subset of Diamondbird/Janz doubled haploid (DH) population showed monogenic segregation, when tested against TTKST and the locus was temporarily named SrJNZ. SrVL-linked markers gwm120 and wmc175 flanked SrJNZ at a similar genetic distance, thereby confirming our hypothesis. Chromosome 2BL carries Sr9, Sr16 and Sr28. Sr9 is a multi-allelic locus and all known alleles of Sr9 and Sr16 are ineffective against TTKSK and its derivatives. A recombination value of 16.7 cM between Sr9g-linked stripe rust resistance gene Yr7 and SrJNZ in Diamondbird/Janz DH population suggested that SrJNZ is not an allele at the Sr9 locus. Based on comparison of published genetic distances between Lr13, Sr9, Sr28 and Sr16 with that observed in this study, we concluded SrVL and SrJNZ to be Sr28. This gene was contributed by a common parent Gabo, which also exhibited resistance against TTKST. Sr28-linked markers gwm120 and wmc175 confirmed the presence of this gene in a high proportion of Australian cultivars that showed stem rust resistance in Kenya. These markers can be used for marker-assisted pyramiding of Sr28 with other stem rust resistance genes.
Keywords: Disease resistance; Markers; Stem rust; Ug99; Wheat